ECONOMICS OF RAISING JERSEY X ASSAM LOCAL CROSSBRED CALVES AT DIFFERENT LEVELS OF PROTEIN IN CALF STARTER - N.K. Sarma; K. Zothanpuii; T.K. Amonge (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Aim of the present investigation was to evaluate the economics of raising Jersey X Assam local crossbred calves reared under three different calf starters containing three different DCP levels. Twelve new born crossbred calves of either sex were randomly divided into three groups and reared under three different calf starters containing three different DCP levels of 20 (group I), 22 (group II) and 24 (group III) per cent with 75-76 per cent TDN. The experimental calves were offered whole milk, green fodder and calf starter as per standard feeding schedule (ICAR, 1991). The calves of group I showed significantly (P<0.05) better body weight gain than group II and group III. The total cost of feeding the calves during the whole experiment period was Rs. 3901.03, 3947.92 and 3934.15 and cost of feeding per kg weight gain was Rs. 100.02, 102.01 and 110.82 in the dietary treatments groups I, II and III respectively. The total cost of feeding was highest in group III due to incorporation of more amount of ground nut cake and soya bean. The lowest cost of feeding in group I may be due to lower intake of milk, and calf starter and lower cost of the calf starter. From the results, it can be inferred that the Jersey x Assam local crossbred calves reared with calf starter containing 20 per cent DCP and 75-76 TDN along with green fodder and limited amount of whole milk would be economical for the optimum performance.